Strategies of immunization of religious beliefs = Nowoczesne strategie immunizacji przekonań religijnych - Sztajer, Sławomir (2020)
The confrontation between religious and nonreligious beliefs and belief systems is often a source of cognitive dissonance. To reduce dissonance, religious individuals use a variety of strategies. The article discusses the main strategies of immunization of religious beliefs and belief systems. It focuses on the logical and epistemological characteristics of religious beliefs as well as on the mental processes and intentional strategies. The immunization strategies discussed here include action such as delegitimization of scientific knowledge, reinterpretations that change the way religion and religious faith are understood, attempts to adapt scientific knowledge to religious thinking, and emphasizing the separation between scientific knowledge and religious faith.
Keywords: Cognitive Dissonance; Immunization; Religious Belief; Worldview